Non-stop autumn migrations of Light-bellied Brent Geese Branta bernicla hrota tracked by satellite telemetry – racing for the first Zostera bite? - Vissing, Marie S.; Fox, Anthony D.; Clausen, Preben (Wildfowl, 2020)
Satellite telemetry tracking of Light-bellied Brent Geese was used to test whether the length of time taken to undertake their autumn migration was longer than the duration of their spring migration (published previously). Spring and autumn migration did not differ significantly and both were conducted almost non-stop, despite expectations that birds would be more time-limited in spring than autumn. Rich feeding opportunities in the arctic prior to autumn departure and large beds of eelgrass Zostera sp. at the final destinations, combined with a lack of suitable Zostera feeding habitat at potential staging areas along the route, most likely explain the rapid and direct autumn migration pattern observed in the population. Although individual goose migrations were fast and of similar duration in the two seasons, autumn migration for the entire population was spaced over a month, in contrast to spring when all birds usually migrated within a 10-day period. From the lack of a difference between tagged and non-tagged individuals in the timing of their migration (the latter based on citizen science observation phenology), we believe the birds’ movements were largely unaffected by their tags.